Cloning, expression and rapid purification of recombinant chicken interferon-alpha - Phuong Thao, Phuong Thi; Van Truong, Le; Chia, Wen Yi; Van Quyen, Dong (Academia Journal of Biology, 2023)
The poultry industry in Vietnam is vulnerable to many viral diseases. Since antibiotics and vaccination provide inadequate protection, it will be beneficial to have alternative immunostimulants to boost non-specific immunity in poultry. Chicken interferon-alpha (ChIFNα) has been described previously with antiviral activity against many pathogens. Therefore, the purpose of this study is to clone and express recombinant ChIFNα in Escherichia coli. The ChIFNα gene was successfully cloned into the pET32a(+) vector, then expressed in the E. coli Rosetta strain. Different expression conditions were tested for the best yield of the expressed protein. Results showed that recombinant ChIFNα was expressed in Rosetta E. coli as inclusion bodies with a yield of 30 mg/100 L culture after induction with 0.5 mM IPTG in 4 hours at 37 oC. The recombinant protein was purified using affinity column chromatography under denaturing conditions with the purity > 94%. Western blot analysis indicated that recombinant ChIFNα reacted specifically with its antibody. Further studies will be carried out to characterize the biological activities of recombinant ChIFNα and its application in the poultry industry.